The potential utility of [68 Ga]Ga-DOTA-FAPI-04 as a novel broad-spectrum oncological and non-oncological imaging agent—comparison with [18F]FDG - Lan, Lianjun; Liu, Hanxiang; Wang, Yingwei; Deng, Jia; Peng, Dengsai; Feng, Yue; Wang, Li; Chen, Yue; Qiu, Lin (European journal of nuclear medicine and molecular imaging, 2022)
Purpose This study aimed to compare the detection performance of [ 68 Ga]Ga-DOTA-FAPI-04 and [ 18 F]FDG PET/CT in the patients with various oncological and non-oncological lesions. Methods A total of 123 patients underwent contemporaneous [ 68 Ga]Ga-DOTA-FAPI-04 and [ 18 F]FDG PET/CT were included in this prospective study. The maximum standard uptake value (SUVmax) was measured to compare oncological and non-oncological lesion uptake. The sensitivity, specificity, predictive values, and accuracy of [ 18 F]FDG and [ 68 Ga]Ga-DOTA-FAPI-04 PET/CT for detecting primary, metastatic, and non-oncological lesions were calculated and compared to evaluate the detection efficacy. Results The study subjects consisted of 123 patients (69 men and 54 women; mean age 56.11 ± 11.94 years). Among the 102 patients with either newly diagnosed (82 patients) or previously treated solid tumor (20 patients), a total of 88 solid primary malignant tumors in 84/102 patients were detected. Two patients had two primary tumors each and 1 patient had three primary tumors. Among them, 58/102 and 43/102 patients had nodal (376 lesions) and distant metastases (406 lesions), respectively. Eight patients had hematological neoplasm. No malignant oncological diseases were detected in the remaining 13 patients. A total of 145 non-oncological lesions and benign tumors in 52/123 patients were detected incidentally. [ 68 Ga]Ga-DOTA-FAPI-04 PET/CT demonstrated a significantly higher uptake and detection rate for the primary (SUVmax 10.98 ± 5.83 vs. 8.36 ± 6.43, p < 0.001; sensitivity 97.67 vs. 84.89%; and accuracy 96.59 vs. 82.95%, X 2 = 0.538, p = 0.021), nodal (SUVmax 10.50 ± 5.98 vs. 8.20 ± 6.29, p = 0.011; sensitivity 97.59 vs. 84.72%; and accuracy 97.34 vs. 84.31%, X 2 = 2.067, p < 0.001), and distant metastatic lesions (SUVmax 9.64 ± 6.45 vs. 6.74 ± 4.83; p < 0.001; sensitivity 98.01 vs. 65.59%; and accuracy 97.04 vs. 65.51%, X 2 = 4.897, p < 0.001) of solid tumor than did [ 18 F]FDG PET/CT. [ 68 Ga]Ga-DOTA-FAPI-04 PET/CT demonstrated a lower activity (SUVmax: 6.84 ± 4.67 vs. 13.09 ± 7.29, p < 0.001) and detection rate (sensitivity 50.65 vs. 96.75%, and accuracy 51.28 vs. 95.51%, X 2 = 5.166, p < 0.001) for multiple myeloma and lymphoma compared to [ 18 F]FDG PET/CT. [ 68 Ga]Ga-DOTA-FAPI-04 and [ 18 F]FDG PET/CT PET/CT demonstrated a comparative activity (SUVmax 6.40 ± 3.95 vs. 5.74 ± 15.78, p = 0.729) and detection efficacy (sensitivity 86.52 vs. 72.34%, and accuracy 84.83 vs. 72.41%, X 2 = 9.460, p = 0.007) for non-oncological lesion and benign tumor detection. Conclusions Except for myeloma and lymphoma, [ 68 Ga]Ga-DOTA-FAPI-04 PET/CT showed a superior detection efficacy for detecting various primary and metastatic lesions than [ 18 F]FDG PET/CT. A comparative detection utility for non-oncological lesion was obtained with both tracers. [ 68 Ga]Ga-DOTA-FAPI-04 could be used as a broad-spectrum tumor and inflammatory imaging agent in the clinical especially for various solid tumors and non-oncological lesions.